H52 A survey on family caregivers' skills and motivations. (12th September 2022) - Galli, Monia; Ponginebbi, Mariarosa; Fontana, Antonio; Invernizzi, Roberta; Alastra, Vincenzo
Abstract : Background: Family caregivers are those who, on a free and continuous basis, take care of non-self-sufficient 'loved ones' (NSSP). Public institutions in Italy advocate that people who are no longer self-sufficient should remain at home, mainly for economic reasons; however, the noble intention is never lacking: keeping the NSSP in the context in which he/she lived and among family affections promotes his/her wellbeing and slows down his/her decline. To help the caregiver take charge of the NSSP, institutions grant economic, regulatory and tax benefits. Case History: The family caregivers' training needs and demands have not been deepened and their training is generally not addressed by the institutions, whereas it is fundamental to the safety and quality of life of: the NSSP, such as Huntington's disease patients for many years after the manifestation of the disease, the caregiver himself. To explore these issues, we have prepared a questionnaire with questions on: the caregiver and the NSSP, the importance of the family caregiver's knowledge of Huntington's disease and its manifestations and implications, what motivates the caregiver and what demotivates him/her, the degree of knowledge, the caregiver thinks to have on the different issues, how and where the caregiver has acquired his/her skills. Conclusions: The survey is in progress and questionnaires are mainly filled in an assisted way. The poster, which we intend to present at the EHDN meeting, will contain statistics on the answers we are gathering, conclusions based on the caregivers' lived experience, training proposals.